Industrial Buyer Innovation Adoption Model: A Focus on a Smartphone-Based Electrochemical Analytical Device for Toxic Heavy Metal Detection - Wasapon Thanabodypath (MDPI AG, 2021)
Smartphone-Based Electrochemical Analytical Devices (SEAD) enable sophisticated toxic heavy metal quantification experiments to be conducted anywhere with high precision, selectivity, and sensitivity. However, a very limited number of such technologies are able to make the transition from the lab to the competitive B2B marketplace. The purpose of this paper is to examine the factors influencing SEAD adoption in the manufacturing industry using the Industrial Buyer Innovation Adoption (IBIA) model, which integrates B2B consumer behavior theories and technology acceptance models from the past 50 years. Analysis of data collected from 400 corporations in Thailand revealed that sellers, buyers, internal organization and invented technology advantage variables predicted industrial innovation adoption based on binary logistic regression. This research contributes to the understanding of SEAD transition from scientific knowledge to sustainable technology and diffusible innovation. The ambitious IBIA framework is potentially an alternative managerial tool for holistically assessing and creating adoptable innovative business models for new technologies.